DEVELOPMENT AND VALIDATION OF A HPLC METHOD FOR DETERMINATION AND QUANTIFICATION OF RUBRAXANTHONE IN STEM BARK EXTRACT OF MANGOSTEEN - Meri Susanti; Dwisesaria Irma Lena; Dachriyanus Dachriyanus (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Rubraxanthone is one of antibacterial and antioxidant compound which is isolated from stem bark of mangosteen (Garcinia mangostana Linn.). The precise method for analysis of plant constituents is normally a reverse-phase high performance liquid chromatographic (RP-HPLC). Development and validation of a RP-HPLC method for chromatographic separation was carried out on a reversed-phase column Shimadzu ® Shimp-pack VP – ODS (4.6x250mm) using an isocratic mobile phase of 0.4% formic acid - acetonitrile at a flow rate 1mL min-1, and detection was with a UV detector. The linearity of the proposed method was found in the range of 2.5-25μg/mL-1 with regression coefficient 0.999. Intraday precision studies showed the relative standard deviation ≤1.58% and inter-day ≤3.20%. Accuracy of the method was determined by a recovery study conducted at 3 different levels, and the average recovery was 102.18%. The Limit of Detection Limit of Quantitation (LOQ) and were 0.47 and 1.56μg/mL-1.The contents of rubraxanthon in the crude was 0.23±0.07%w/w.